Morbidity and Mortality in Preterm Newborns Under 32 Weeks in a Neonatal Intensive Care Unit in the city of Bogotá (Colombia) (Universitas Medica, 2021)
ABSTRACTIntroduction: Adverse neonatal outcomes are associated with a great economic cost to health systems. There is growing concern about the directly proportional relationship between the number of survivors and the disability rates of preterm infants. The objective was to describe the morbidity and mortality in newborns less than 32 weeks of gestational age and to determine the associated factors. Materials and methods: Cross-sectional study with an analytical component, which included all preterm newborns under 32 weeks of gestational age, who were born between January 2018 and December 2020 and who continued their follow-up in the Mother Kangaroo program of the same institution. Results:108 newborns were identified. The main outcomes were bronchopulmonary dysplasia with a frequency of 85.9% among survivors and an overall mortality of 27.7%. The strong association between septic shock and death is highlighted (ORa = 275; p = 0.004); in the same sense, gestational age (ORa = 83.3; p = 0.004). Conclusions: The incidence of BPD in preterms younger than 32 weeks is high, constituting the most important morbidity in this group, with a significant associated global mortality. In terms of mortality the probability of dying in these newborns is explained by lower gestational age (